2018
DOI: 10.1016/j.saa.2017.08.068
|View full text |Cite
|
Sign up to set email alerts
|

Spectral and computational features of the binding between riparins and human serum albumin

Abstract: The green Brazilian bay leaf, a spice much prized in local cuisine (Aniba riparia, Lauraceae), contains chemical compounds presenting benzoyl-derivatives named riparins, which have anti-inflammatory, antimicrobial and anxiolytic properties. However, it is unclear what kind of interaction riparins perform with any molecular target. As a profitable target, human serum albumin (HSA) is one of the principal extracellular proteins, with an exceptional capacity to interact with several molecules, and it also plays a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 36 publications
1
5
0
Order By: Relevance
“…The K a for the three temperatures remained close to the order of magnitude of 10 4 M −1 . According to the literature, this meant that the binding constant was moderate for the albumin proteins from different species [32,33,34]. The number of sites, n, remained close to the unity, which was in concordance with the first order binding equilibrium model.…”
Section: Resultssupporting
confidence: 72%
See 2 more Smart Citations
“…The K a for the three temperatures remained close to the order of magnitude of 10 4 M −1 . According to the literature, this meant that the binding constant was moderate for the albumin proteins from different species [32,33,34]. The number of sites, n, remained close to the unity, which was in concordance with the first order binding equilibrium model.…”
Section: Resultssupporting
confidence: 72%
“…Such methods (binding equilibrium model and IDF) showed that, although the results obtained were in the same order of magnitude for the binding constant 10 4 M −1 , the same could not be said about the number of sites. Such results showed that both methods had reasonable agreement, revealing that the complex had an affinity constant that relayed between 10 4 –10 6 M −1 , which was a moderate constant for most of the albumin proteins [32,33,34]. Although the binding constant (K b ) obtained from the Scatchard plot had the same order of magnitude of K a obtained from the double log plot, the difference between the number of binding sites indicated that the IDF method was more realistic.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…To us this suggests that many of the citing authors have not read our article in sufficient detail, or did not understand it. In connection to the double log equation alone, we found seven more publications that inappropriately cite our paper unequivocally and directly in support of their use and/or interpretation of the double log equation in terms of the number of binding sites [8][9][10][11][12][13][14]. We do note that one of these articles, upon our request, has been corrected, in the sense that the inappropriate reference to our work in support of the double log equation has been removed [14].…”
mentioning
confidence: 89%
“…The binding constant ( K b ) and the number of binding sites ( n ) of Pyr and 1-OHPyr with BSA in binary and ternary interaction systems could be calculated by fitting the curve based on Eq. (2) [3] , [4] .
Fig.
…”
Section: Datamentioning
confidence: 99%